Validitas Instrumen Assesmen (Analisis Validitas Isi dan Konstruk Instrumen Asesmen Buku Pelajaran Al Quran Hadis Kelas 6 Madrasah Ibtidaiyah Materi Surat Ad Dhuha Bab VI) - Muhammad Afifullah Nizary; Ahmad Nur Kholik (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2021)
This article attempts to examine how to analyze the validity of the assessment instrument. In fact, not all teachers are able to make the correct instruments. Many teachers only take instruments from other schools to be used as a tool in measuring their students, even though the same instrument is not necessarily a measuring instrument with different objects. This habit needs to be improved. The teacher should be able to make their own instruments, because the teacher knows best about the differences in the abilities of each student. When the teacher uses instruments from other schools, where there are parts that the teacher has not conveyed in class, the students themselves are the losers. In making an assessment instrument the teacher must pay attention to two characteristics. Namely validity and reliability. Validity itself is divided into content validity, construct validity, and eksternal validity. Each validity has its own characteristics.